Testing the Seamount Refuge Hypothesis for Predators and Scavengers in the Western Clarion-Clipperton Zone - Leitner, Astrid B.; Drazen, Jeffrey C.; Smith, Craig R. (Frontiers in Marine Science, 2021)
Seamounts are common in all ocean basins, and most have summit depths >3,000 m. Nonetheless, these abyssal seamounts are the least sampled and understood seamount habitats. We report bait-attending community results from the first baited camera deployments on abyssal seamounts. Observations were made in the Clarion Clipperton Zone (CCZ), a manganese nodule region stretching from south of Hawaii nearly to Mexico. This zone is one of the main target areas for (potential) large-scale deep-sea nodule mining in the very near future. The Seamount Refuge Hypothesis (SRH) posits that the seamounts found throughout the CCZ provide refugia for abyssal fauna likely to be disturbed by seabed mining, yielding potential source populations for recolonization of mined areas. Here we use baited cameras to test a prediction of this hypothesis, specifically that predator and scavenger communities are shared between abyssal seamounts and nearby abyssal plains. We deployed two camera systems on three abyssal seamounts and their surrounding abyssal plains in three different Areas of Particular Environmental Interests (APEIs), designated by the International Seabed Authority as no-mining areas. We found that seamounts have a distinct community, and differences in community compositions were driven largely by habitat type and productivity changes. In fact, community structures of abyssal-plain deployments hundreds of kilometers apart were more similar to each other than to deployments ∼15 km away on seamounts. Seamount communities were found to have higher morphospecies richness and lower evenness than abyssal plains due to high dominance by synaphobranchid eels or penaeid shrimps. Relative abundances were generally higher on seamounts than on the plains, but this effect varied significantly among the taxa. Seven morphotypes were exclusive to the seamounts, including the most abundant morphospecies, the cutthroat eel Ilyophis arx. No morphotype was exclusive to the abyssal plains; thus, we cannot reject the SRH for much of the mobile megafaunal predator/scavenging fauna from CCZ abyssal plains. However, the very small area of abyssal seamounts compared to abyssal plains suggest that seamounts are likely to provide limited source populations for recolonizing abyssal plains post-mining disturbance. Because seamounts have unique community compositions, including a substantial number of predator and scavenger morphospecies not found on abyssal plains, they contribute to the beta biodiversity of the Clarion-Clipperton Zone, and thus indirect mining impacts on those distinct communities are of concern.